Living Kidney Paired Exchange Transplant Program in Portugal – A successful example - Ribeiro, Catarina Isabel (2019)
Up to 30% of living donor pairs are not transplanted for mismatch ABO group and/or system Hu-man Leukocyte Antigen (HLA). Kidney paired exchange donation national programs emerged as a strategy to try to overcome these barriers. In Portugal, the Kidney Paired Exchange Donation National Program (KPEDNP) was legislated in 2010, and the first living kidney paired exchange transplant occurred in 2013. So far 22 transplants have been performed. Purpose: The present work aims to assess the characteristics and evolution of patients submitted to kidney paired ex-change transplant in Portugal. Methods: The authors present a retrospective observational study with analysis of respective patients. Results: Of the total sample, most recipients were male (55%), with a median age of 53 years. Renal polychistosis was the etiology of the most common kidney disease (18%) and most patients were previously on chronic hemodialysis (68%). Three patients had calculated Panel Reactive Antibody (PRAc) higher than 98% and 10 had higher than 80% PRAc. Anti-Thymocyte Globulin (ATG) immunosuppression was induced in 50% of patients and Rituximab and/or plasmapheresis immunomodulation in 15%. All recipients pre-sented immediate graft function. There were no major complications, with minor events at 15%. At a median follow-up time of 27 [2-46] months there were no cases of acute cell rejection and only one case of humoral rejection. Donor and recipient survival rates were both 100%. Conclusion: These excellent preliminary results aim to stimulate the increase in the number of pairs to include in the KPEDNP and a larger number of transplants performed in this program. As a significant part of this sample, living-kidney paired exchange transplant may be a possibility for patients with HLA and/or ABO group incompatibility. Kidney paired exchange donation enhances life donation and offer to incompatible and selected pairs an opportunity of successful kidney transplantation.